Nghiên cứu chế tạo vật liệu gốm xốp trên cơ sở vi hạt thủy tinh cầu rỗng và gốm kết dính berlinite (AlPO4) làm vỏ cách nhiệt cho pin nhiệt - Sơn, Lương Trung; Thảo, Phạm Mạnh; Kỳ, Nguyễn Văn; Toán, Lê Văn (Vietnam Journal of Chemistry, 2016)
The present work shows the manufacturing porous ceramics based on the berlinite-bonded alumina ceramics (AlPO4) with the addition of hollow glass microspheres, Al2O3 and Cr2O3. The prepared ceramics was characterized by XRD, TGA and SEM. Results showed the desired ceramics was obtained at rather low temprature with density of 0.30 to 0.40 g.cm-3 and its conductivity coefficient is of 0.10 to 0.12 W.m-1.K-1. Produced ceramics was successfully used to make the insulation shell for two kinds of thermal batteries. Keywords. Porous ceramic, insulation, thermal battery.